2022
DOI: 10.5435/jaaos-d-22-00089
|View full text |Cite
|
Sign up to set email alerts
|

Instagram Use Among Orthopaedic Surgery Residency Programs

Abstract: Introduction:The COVID-19 pandemic created unprecedented challenges to residency recruitment. With in-person away rotations prohibited and interviews held virtually, orthopaedic residency programs turned to social media. Studies document the exponential growth of residency program Instagram accounts after March 2020, but few analyze the content of their posts. This study provides an updated assessment of such Instagram accounts including a detailed analysis of their content and a discussion of potentially conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Two studies reported on what content was being posted on Instagram by residency programs. One found that Instagram posts often featured resident introductions, content about camaraderie, and the resident social lives 41 . Another study found that 54% of Instagram posts contained departmental content, 13% were social posts, and 10% were related to COVID-19 42 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies reported on what content was being posted on Instagram by residency programs. One found that Instagram posts often featured resident introductions, content about camaraderie, and the resident social lives 41 . Another study found that 54% of Instagram posts contained departmental content, 13% were social posts, and 10% were related to COVID-19 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, social media use, particularly Instagram, among orthopaedic residencies skyrocketed during the pandemic 30,38 . Lifestyle became highly valued because posts demonstrating social lives of residents were of particular importance to applicants 30,[40][41][42][43][44][45][46] . Although some programs may decrease their use of social media with the return of traditional recruiting, the pandemic ultimately caused refinement of program social media accounts and residency websites that will serve as valuable recruiting tools for residency applicants going forward.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 This is highlighted in the dramatic rise of Instagram accounts by residency programs to build community and connect with potential future residents. 2,3 While several studies have explored Instagram use in graduate medical education and recruitment, there is a paucity of literature on Instagram use for undergraduate medical education and medical student life. The objective of this study is to explore and analyze engagement with an undergraduate medical student life Instagram account at a single institution.…”
mentioning
confidence: 99%